Ensuring gender and social equity in health: an analysis of Nigeria's Social Health Insurance Scheme and Basic Health Care Provision Fund - Iboro Nelson (Elsevier, 2020)
Background: It is expected that a well-functioning, pre-paid health financing system that aims to move a country towards universal health coverage (UHC) will be equitable and gender-balanced. However, this feature is not automatic; much depends on the policy environment, including legal frameworks, implementation design, and management of the health financing scheme. To move towards UHC, Nigeria is implementing two key reforms: the Basic Health Care Provision Fund (BHCPF) and Social Health Insurance Scheme (SHIS). The BHCPF was created under the 2014 National Health Act to provide a basic package of health care to all Nigerians. Here, I report on a review of policy and legal frameworks at the policy formulation stage of the reforms, with a focus on gender and equity. Methods: I used findings from Abia state gender and equity analysis conducted to identify gender-related and equity-related barriers and opportunities in the design and implementation of the BHCPF and SHIS. I undertook project monitoring of the early-stage policy formulation phase of the reforms across functional areas of governance, revenue generation, risk pooling, enrolment strategies, and health benefit package. Findings: Initial assessment results showed several service delivery barriers to gender parity in staff (men in leadership and women in service delivery positions), low level of male engagement, lack of youth-friendly health services, unavailability of gender-based violence services, and low level of knowledge and understanding of gender and equity issues among key state-level implementing institutions. But early intervention results showed that progress has been made in the inclusion of men and women in the governance of the scheme, the establishment of an equity fund to subsidise those who are too poor to pay and progressive financial contributions into the scheme based on the ability to pay, and a central pooling of risk. Furthermore, a sustainable effort towards bridging the knowledge gap of key health-care professionals and policymakers in gender and equity issues in health has been instituted by national government implementing agencies with the mainstreaming of gender issues in the BHCPF manual and followed through with trainings of community representatives and health service providers. Interpretation: UHC is hinged on gender and social equity in access to health-care services. Efforts to achieve this must begin at the policy formulation stage and carry through to policy implementation. However, UHC does involve political trade-offs and the degree to which implementation practice will conform to policy directions already set out is yet to be seen. Funding: USAID through Health Policy Plus (HP+) implemented by Palladium.